2020
DOI: 10.1093/cvr/cvaa233
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of hypertrophic cardiomyocytes identifies new players in pathological remodelling

Abstract: Aims Pathological cardiac remodeling is characterized by cardiomyocyte hypertrophy and fibroblast activation, which can ultimately lead to maladaptive hypertrophy and heart failure (HF). Genome-wide expression analysis on heart tissue has been instrumental for the identification of molecular mechanisms at play. However, these data were based on signals derived from all cardiac cell types. Here we aimed for a more detailed view on molecular changes driving maladaptive cardiomyocyte hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…7 c,e; 8 a,e; Supplemental Tables 6 – 7 ). The most dysregulated gene in myectomy tissue was RASL11B 58 (log2FC 1.72), which has been associated with pathologic cardiac hypertrophy 58 in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…7 c,e; 8 a,e; Supplemental Tables 6 – 7 ). The most dysregulated gene in myectomy tissue was RASL11B 58 (log2FC 1.72), which has been associated with pathologic cardiac hypertrophy 58 in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological cardiac hypertrophy is a common predecessor to heart failure. 35 A recent study reported the transcriptomic differences of cardiomyocytes between early (hypertrophic cardiomyocytes) and maladaptive phage (failing cardiomyocytes) of cardiac remodeling in pressure overload-induced mouse models, 36 Through pseudo-temporal ordering, we identified the transcriptomic dynamics during the transition towards the failing state of cardiomyocytes in HCM of human patients (Figure 2I). Based on multiple lines of evidence from independent analyses, we obtained a list of genes that could serve as potential medical targets for mitigating the progression of heart failure in HCM (Figure 2J), and most have not been implicated in heart failure or cardiac hypertrophy such as FGF12 , IL31RA , BDNF and PROS1 .…”
Section: Discussionmentioning
confidence: 95%
“…Our interrogation of independent RNA expression data and western blot data shows consistent upregulation in Sorbs2 across a range of myocardial diseases, as has been recently noted. 73 Further, Sorbs2 protein is upregulated in LVNC, 8 diabetic cardiomyopathy, 6 and is released from infarcted myocardium. 4 Upregulation is potentially mediated by Mef2 transcription factors, 74 although posttranscriptional regulation by disease-relevant microRNAs and RNA-binding proteins may also contribute.…”
Section: Clinical Relevance Of Sorbs2 In Cardiac Diseasementioning
confidence: 99%